Tatalaksana Farmakologi takiaritmia supraventrikel pada pasien dengan pembesaran jantung kanan: Serial kasus - Hendiperdana, Mochamad Rizky (Jurnal Kardiologi Indonesia, 2025)
Background Right atrial (RA) enlargement is a common finding in patients with pulmonary hypertension (PH). Supraventricular arrhythmia (SVA) is common in PH patients with RA enlargement. Treatment of SVA should be aggressive since it can cause hemodynamic worsening consequences because RA function plays an important role in right heart function. Case Illustration Three cases of SVA in underlying right heart enlargement with preserved ventricular function that successfully managed by pharmacological cardioversion according to the guidelines. The first case describes atrial flutter with right bundle branch block (RBBB) morphology which successfully converted to sinus rhythm by amiodarone (class III antiarrhythmic drug) administration, meanwhile the second and third cases demonstrate paroxysmal SVA that converted to sinus rhythm by diltiazem (class IV antiarrhythmic drug) administration. Conclusion Supraventricular arrhythmia is a frequent arrhythmia that occurs in pulmonary hypertensive and right heart dilation patients. The tachyarrhythmia in this patient population tolerated poorly and led to hemodynamic perturbation. Pharmacological cardioversion is one of the effective approaches to alleviate patient symptoms with significant clinical improvement.